Metagenomic assessment of the Cebus apella gut microbiota. Issue 10 (26th June 2019) - Firrman, Jenni; Liu, LinShu; Tanes, Ceylan; Bittinger, Kyle; Mahalak, Karley; Rinaldi, William
Abstract: Cebus Apella ( C. apella ) is a species of Nonhuman Primate (NHP) used for biomedical research because it is phylogenetically similar and shares anatomical commonalities with humans. Here, the gut microbiota of three C. apella were examined in the different regions of the intestinal tract. Using metagenomics, the gut microbiota associated with the luminal content and mucus layer for each intestinal region was identified, and functionality was investigated by quantifying the levels of short chain fatty acids (SCFAs) produced. The results of this study show a high degree of similarity in the intestinal communities among C. apella subjects, with multiple shared characteristics. First, the communities in the lumen were more phylogenetically diverse and rich compared to the mucus layer communities throughout the entire intestinal tract. The small intestine communities in the lumen displayed a higher Shannon diversity index compared to the colon communities. Second, all the communities were dominated by aero‐tolerant taxa such as Streptococcus, Enterococcus, Abiotrophia, and Lactobacillus, although there was preferential colonization of specific taxa observed. Finally, the primary SCFA produced throughout the intestinal tract was acetic acid, with some propionic acid and butyric acid detected in the colon regions. The small intestine microbiota produced significantly less SCFAs compared to the communities in the colon. Collectively, these data provide an in‐depth report on the composition, distribution, and SCFA production of the gut microbiota along the intestinal tract of the C. apella NHP animal model. Abstract : Research Highlights: The gut microbiota community of the C. apella was dominated by aero‐tolerable taxa such as Streptococcus, Enterococcus, Abiotrophia, and Lactobacillus. The communities that developed within the luminal content and mucus layer of the C. Apella intestinal tract were divergent from each other, with the lumen having more phylogenetic diversity and richness than the mucus communities. Functionally, the C. apella colon communities produced significantly more short chain fatty acids (SCFAs) than the small intestine communities. The primary SCFA produced was acetic acid, with small levels of propionic acid and butyric acid detected in the colon regions.